2010
DOI: 10.1002/asl.260
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for perturbing surface initial conditions in LAMEPS

Abstract: The lack or inadequate representation of uncertainties in the surface initial conditions (ICs) affects the quality of ensemble forecast, in particular the near surface temperature and precipitation. In this paper, a strategy for perturbing surface ICs in limited area model ensemble prediction system, noncycling surface breeding (NCSB) is proposed. The strategy combines short-range surface forecasts driven by perturbed atmospheric forcing and the breeding method for generating the perturbation to surface ICs. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Further, the use of NCSB ensures larger consistency in the surface coupling of ALADIN with ECMWF, which improves the forecast quality. Wang et al (2010) showed that the positive impact of NCSB can be achieved for the lower-atmospheric variables, such as those at 850 hPa.…”
Section: Verification Of Upper-air Weather Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the use of NCSB ensures larger consistency in the surface coupling of ALADIN with ECMWF, which improves the forecast quality. Wang et al (2010) showed that the positive impact of NCSB can be achieved for the lower-atmospheric variables, such as those at 850 hPa.…”
Section: Verification Of Upper-air Weather Variablesmentioning
confidence: 99%
“…The detailed description and discussion of blending, in particular the technical implementation in ALADIN-LAEF and details on the tuning of the breeding-blending cycle, are given in Bellus (2008) and Bellus et al (2010).…”
Section: Blending Large-scale Perturbations From Svs and Small-scale mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Ensemble systems and data 2.1 The regional ensemble ALADIN-LAEF ALADIN-LAEF is the operational regional ensemble system of ZAMG and runs at ECMWF (Wang et al, 2010. It is based on the hydrostatic spectral limited area model AL-ADIN ).…”
Section: Introductionmentioning
confidence: 99%
“…The main emphasis is put on the variation and tunings of the following schemes and parameterizations: the diagnostic convection scheme as described in Bougeault (1985); the prognostic deep convection scheme 3MT (modular multiscale microphysics and transport scheme; Gerard et al, 2009), and the connected microphysics scheme described in Geleyn et al (2008) and Gerard et al (2009); the radiation scheme based on Ritter and Geleyn (1992) or alternatively the scheme described in Mlawer (1997) and Morcrette (1991); the pseudo-prognostic TKE (turbulent kinetic energy) scheme described in Vana et al (2008). Further details can be found in Wang et al (2010). Authors are aware that the forecasts of the individual members produced by the multi-physics approach cannot be regarded as equally likely.…”
Section: Introductionmentioning
confidence: 99%